Social dialogue in education in Latin America:a regional survey - Gajardo, Marcela (2005)
The ILO’s Sectoral Activities Department commissioned the research leading to this Working Paper in preparation for the Eighth Session of the Joint ILO/UNESCO Committee of Experts on the Application of the Recommendations concerning Teaching Personnel (CEART), held from 15-19 September 2003 in Paris. The CEART has for some time been concerned with the issue of teachers’ participation in education reforms through information sharing on changes, consultation on educational policy and collective bargaining negotiations on teaching and learning conditions. It therefore requested the ILO to prepare thematic reports on forward-looking procedures and structures to encourage participation of teachers and teachers’ organizations in education reform decisions. A series of regional reports were commissioned, of which this study is one.